The relationship between social competence and emotional control on career choices at Kepanjen Islamic High School: Hubungan Kompetensi Sosial Dan Kontrol Emosi Terhadap Pemilihan Karir SMA Islam Kepanjen - Kholisna, Titin; Effendi, Moch. Zulham (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Raden Rahmat Malang, 2025)
Abstract Adolescents in a phenomenon within the school environment found concerns from researchers, this competence (communication style) can include difficulty expressing ideas in the discussion process, emotional control (affective feelings), the presence of stimulus from the friendship process in school, career choice (how to making a decision) means that after graduating from school the right goal is. Therefore, this research is considered important to test whether there is a relationship between one variable or another and existing theoretical concepts. The aim of this research is to find out whether there is an influence of social competence on career choices at Kepanjen Islamic High School. To find out whether there is an influence of emotional control on Kepanjen Islamic High School students' career choices. To find out whether there is an influence of social competence and emotional control on the career choices of Kepanjen Islamic High School students The method used is the correlational method by proving the existence of a relationship between social competence and emotional control on career choice with data collection methods in the form of questionnaires, interview observations with analysis tests using validity and reliability tests, correlation tests and hypothesis tests. The result is that the correlation between social competence and the person's career choice is >0.501 with a score that can be said to be very significant in relation. Emotional control is related to career choice as proven by the person's results > 0.650 with a score that can be said to be very significant in this relationship. Social competence and emotional control are related to career choice as proven by the person's results > 0.577 and 0.501 and 0.650 with a minimum score of 0.05 which can be said to be very significant in this relationship. For teachers, map those who have low or high social competence as well as emotional control for students' career choices. In this case, teachers can map out who they want to continue their education or work and get married. in a social context, the school collaborates with related agencies to accommodate extensive and sustainable career information to innovate to conduct further studies with various parties in order to open mutual aid between the two parties. Key words: social competence, emotional control, career choice